Figurative Language Analysis Of Lado Ceremony In Kloangpopot Community In Doreng District Sikka Regency - Prisila Ninayanti Bala; Nur Syamsiyah Ekhsan; Yanto Yanto (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Lado ceremony is a local cultural tradition carried out from generation to generation by the people of Kloangpopot community in Doreng district Sikka regency. This paper aims to determine how the process of the lado ceremony the types of figurative language and the meaning of figurative language used in the lado ceremony. Lado ceremony in Kloangpopot community is still implemented until now, where local people still believe in the lado ceremony as a way to fortify the rain during certain events, one of which in a wedding ceremony. The research method used in this Paper is a descriptive qualitative method, which uses data collection methods through observation and interview. The results showed that the Lado ceremony in the Kloangpopot community has several stages of the implementation process, starting from the preparation stage including ordering Pawang hujan services, preparing media tools and materials, then the core stage includes the implementation of the Lado ceremony carried out by the pawang hujan, then the closing stage of handing over souvenirs from the host to the pawang hujan as a form of gratitude for helping so that the host’s event process runs smoothly without rain. In the Lado ceremony there are also types of figurative language and their respective meanings, namely personification simile and repetition, the dominant type of figurative language is personification.